Critical analysis of assessment methodologies for intraorganizational sustainability - Satolo, Eduardo Guilherme [UNESP]; Simon, Alexandre Tadeu (Emerald, 2015)
Purpose – Sustainability is in vogue nowadays. It is a new concept and it has yet to be studied in more depth and rigor to create a stronger understanding. There are several lines of research and development in this area, each one using a specific template for measuring sustainability what poses even greater difficulties to those interested in the subject. The purpose of this paper is to discuss and compare current models for measuring organizational sustainability. Design/methodology/approach – The paper presents a literature review identifying six models that have synergies in their structures and methods for measuring sustainability. It also analyzes each model highlighting key individual features identifying similarities and differences. Findings – Results indicates it is necessary to improve existing models and gathering positive features of each model may be the starting point for obtaining a measurement model of sustainability. Research limitations/implications – This work is restricted to perform a critical analysis of models for measuring intra-organizational sustainability. Originality/value – This is one of the first studies to investigate models that assess sustainability from the intra-organizational perspective.
Keywords: Assessment methodologies; Intra-organizational sustainability; Sustainability; Sustainability dimensions; Sustainability index; Sustainability measurement